Exploring Providers' Perception to Naloxone Education for Opioid Overdose After Receiving Academic Detailing at the U.S. Department of Veterans Affairs. (June 2023) - Bounthavong, Mark; Christopher, Melissa L. D.; Veenstra, David L.; Basu, Anirban; Devine, Emily Beth
Introduction: The U.S. Department of Veterans Affairs (VA), in partnership with the Opioid Overdose Education and Naloxone Distribution (OEND) Program, implemented the National Academic Detailing Service to deliver naloxone education to providers with patients at-risk for opioid-related overdose.Methods: We administered a 26-item online survey to VA providers to explore their perceptions about prescribing naloxone for opioid overdose emergencies and their experience with academic detailing between August 2017 and April 2018. Responses were analyzed using descriptive statistics to (1) explore their current perceptions of naloxone prescribing and their experience with academic detailing, (2) identify differences across provider types [primary care providers (PCP), specialists, and others], and (3) assess perceived naloxone prescribing behavior change after an academic detailing visit.Results: Providers (N = 137) indicated that they were practicing at a level that was consistent with VA goals to promote take-home naloxone to reverse opioid-related overdose events. Average domain scores were similar across PCP, specialist, and other provider types. Specialists reported a higher average attitude domain score (+.56, P = .011) and perceived barriers domain score (+.82, P = .009) than PCPs. Most providers agreed that they prescribed naloxone more frequently due to academic detailing (53%) and indicated that they synthesized information from the academic detailer to change their naloxone prescribing practice (60%).Discussion: VA providers' perceptions of take-home naloxone were aligned with current evidence-based practice. Moreover, providers reported increasing their naloxone prescribing and synthesizing OEND-related information after an academic detailing interaction. Understanding providers' perceptions can be used to improve and enhance the academic detailing program's effectiveness.